Internet advertising vs traditional media a comparison on its effectiveness on UPV-CM students - Albay, Mea Jane.; Hingco, Janette; Laserna, Maegil; Monte, Ivan. (2001.)
This paper studies one of the moving forces of commercialization : advertising. This paper focuses on Internet advertising as an emerging genre of advertising. This paper is primarily an analysis of whether advertising on the Internet is as effective as advertising through traditional media. The researchers see Internet advertising as an alternative to traditional media. Through this research project, the researcher asked 130 UPV-CM student questions regarding media exposure and preference. Questions gaauging advertising effectiveness were also asked. This paper shows that UPV-CM students still preferred traditional media over the Internet with the televisisons as the most preferred advertising medium followed by print, then radio. However, variables used to assess effectiveness were found to have no concrete bearing on advertising effectiveness. Based on the the collected data, the researchers present recommendations focusing on further advertising effectiveness researches. The researcher emphasized on using other variables in determining effectiveness, this, in order to specifically point out the spelling force in advertising.
Research Paper (BA 200 - Business Research) -- [Iloilo City : University of the Philippines in the Visayas - College of Management], March 30, 2001.